Nobody's gonna slow me down? The effects of a transportation cost shock on firm performance and behavior - Catarina Branco; Dirk Dohse; Jo\~ao Pereira dos Santos; José Tavares (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
This paper takes a deep and comprehensive look into the firm-level behavioral reactions to a massive transportation cost shock. Exploiting rich data encompassing the universe of Portuguese private firms and a natural experiment we find that the introduction of tolls on previously toll-free highways caused a substantial decrease of turnover and firm profits. In response to the tolls, firms reduced expenses, cutting employment-related expenses and purchases of other inputs in a similar magnitude. Labor costs were reduced by employment cuts rather than by wage cuts. We find evidence for increased firm exit in treated municipalities, but not for increased re-location. – – In diesem Papier werden die Verhaltensreaktionen auf Unternehmensebene auf einen massiven Transportkostenschock untersucht. Auf der Grundlage umfangreicher Daten portugiesischen Privatunternehmen und eines natürlichen Experiments finden wir heraus, dass die Einführung von Mautgebühren auf zuvor mautfreien Autobahnen zu einem erheblichen Rückgang des Umsatzes und der Unternehmensgewinne führte. In Reaktion auf die Maut senkten die Unternehmen ihre Ausgaben, indem sie beschäftigungsbezogene Ausgaben und Käufe anderer Vorleistungen in ähnlicher Größenordnung zurückfuhren. Dabei wurden die Arbeitskosten eher durch Beschäftigungsabbau als durch Lohnkürzungen reduziert. Wir finden Belege für vermehrte Firmenaustritte in den untersuchten Gemeinden, aber nicht für eine verstärkte Verlagerung.
Keywords: R48; L25; R12; 330; road tolls; infrastructure; firm performance; firm behavior; location; Portugal